INDEPENDENT LEARNING AS AN EFFECTIVE TEACHING METHOD FOR FOREIGN LANGUAGES - Khadjibaeva Shakhzoda Fakhretdinovna; Khadjibayev Sa’dulloh; Iskenderova Kamola Azamatovna (Scientific Impulse, 2023)
Foreign language study has become an inseparable part of the professional training of specialists of various profiles in modern society, and the quality of their language training is often dependent on the successful resolution of issues of professional growth and expansion of contacts with foreign partners. This article discusses the importance and role of independent learning as well as effective methods for teachers and language learners.